2020
DOI: 10.1186/s12963-020-00223-2
|View full text |Cite
|
Sign up to set email alerts
|

Estimating completeness of national and subnational death reporting in Brazil: application of record linkage methods

Abstract: Background In Brazil, both the Civil Registry (CR) and Ministry of Health (MoH) Mortality Information System (SIM) are sources of routine mortality data, but neither is 100% complete. Deaths from these two sources can be linked to facilitate estimation of completeness of mortality reporting and measurement of adjusted mortality indicators using generalized linear modeling (GLM). Methods The 2015 and 2016 CR and SIM data were linked using deterministic methods. GLM with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 16 publications
0
22
0
2
Order By: Relevance
“…C-RC study results are themselves subject to limitations which may bias their age-specific accuracy, especially if the assumption of the independence of sources is violated. In the Brazil study, however, the generalised linear models used included several covariates that reduced any bias from source dependency [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…C-RC study results are themselves subject to limitations which may bias their age-specific accuracy, especially if the assumption of the independence of sources is violated. In the Brazil study, however, the generalised linear models used included several covariates that reduced any bias from source dependency [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…We firstly compare the two approaches using results from a C-RC study in Brazil, because it provides independent and direct source information of mortality indicators and age-specific completeness that do not rely on MLTs [ 14 ]. That C-RC study matched registered deaths to deaths reported in the Ministry of Health (MoH) Mortality Information System (SIM), an independent source.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations